Economic Efficiency (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Economic efficiency is when all goods and factors of production in an economy are distributed or allocated to their most valuable uses and waste is eliminated or minimized. A system is considered economically efficient if the factors of production are used at a level at or near their capacity.